Gelatin Application of Nile Tilapia (Oreochromis niloticus) Bone to The Quality of The Jelly Candy - Maryani Maryani; Titi Surti; Ratna Ibrahim (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2010)
The characteristic of a jelly candy is sweet in taste and has elastic texture. The elastic texture due to gelling agent addition such as carrageenan, sea weed, gum arabic, and gelatin. The Utilization of nile tilapia bone as the source of gelatin product is away to prevent gelatin that is not halal. The aim of the research was to know the concentration of nile tilapia bone gelatin which produced the best quality of jelly candies based on physical chemical characteristic as well as the member of Escherichia coli and hedonic value. The experiment was designed using a Completely Randomized Design with 3 treatments (9%, 10%, 11%) of nile tilapia bone gelatin concentrations. Each treatment was done in triplicate. Data of elasticity, moisture content, water activity, pH, sugar contents were analyzed with Analysis of Varians (ANOVA). A Honestly Significant Difference (HSD) test was conducted to find out the difference among the treatments. The data of hedonic quality was analyzed by a Kruskall Wallis test and continued by a Multiple Comparison. The result showed that the addition of 10% nile tilapia bone gelatin produced the best quality product which had the elasticity (14.20 Newton); moisture content (17.06%); Aw 0.785; pH 4.78; sugar content (48.23%); hedonic (8.13) and the product did not content Escherichia coli bacteria. Key Words : Jelly Candy, Nile Tilapia Bone Gelatin, Quality